2009
DOI: 10.1542/neo.10-12-e600
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Approach to Hypotonia in the Neonate

Abstract: Describe the genetic approach to hypotonia in the newborn. 2. Discuss the most common presentations of genetic disorders associated with hypotonia in the newborn period. 3. Review the genetic basis of neuromuscular disorders that present with hypotonia in the newborn period. 4. Understand the definition of anticipation with respect to trinucleotide repeat disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Differentia diagnosis should be performed in neonatal dystonia with other hereditary diseases. Zadeh et al (18) summarized the related genetic diseases and corresponding detection methods. The details were as follows: Prader-Willi syndrome: methylation analysis or SNRPN expression, and then high-resolution chromosome analysis.…”
Section: Child Patientmentioning
confidence: 99%
“…Differentia diagnosis should be performed in neonatal dystonia with other hereditary diseases. Zadeh et al (18) summarized the related genetic diseases and corresponding detection methods. The details were as follows: Prader-Willi syndrome: methylation analysis or SNRPN expression, and then high-resolution chromosome analysis.…”
Section: Child Patientmentioning
confidence: 99%
“…A comprehensive genetic analysis provided a molecular diagnosis in 80.8% (21/26) of cases. Whereas CMA had a low yield for detecting hypotonic conditions (8.0%, 2/25), WES had a high yield (87.5%, 14/16), highlighting its essential role in the investigation of suspected hypotonia 1,21,61 . A recent study by AlBanji et al 21 found CMA to be diagnostic in hypotonic conditions in 9% of cases and WES in 59%.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hypotonia is defined as reduced resistance to passive range of motion that is present at birth 1,2 . The phenotypic spectrum of hypotonia is broad, including a range of severity, gestational age at onset and associated anomalies [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…İki aylıkken hipotoni ve solunum sıkıntısı nedeniyle hastanemize başvuran bir hastada yüksek CK düzeyi, EKG'de kısa P-R mesafesi, akciğer grafisinde kardiyomegali saptanması sonrasında yurt dışına gönderilen asit maltaz düzeyinin düşük bulunması nedeniyle Pompe tanısı konularak enzim tedavisine başlanmış ancak hasta kaybedilmiştir (15). Periferik hipotonisinin ön planda olması dikkat çekicidir.…”
unclassified